Assessing the latest advances in bone marrow stem cell therapy for Avascular Necrosis hip: A comprehensive systematic review, meta-analysis, and meta-regression of randomized controlled trial studies - Robin Novriansyah; Tanti Ajoe Kesoema; Kevin Christian Tjandra; I. Nyoman Sebastian Sudiasa; Shakira Amirah; Imke Maria Del Rosario Puling; Prudence Lucianus; Revina Maharani; Danendra Rakha Putra Respati; Laksmana Adi Krista Nugraha; Ismail Hadisoebroto Dilogo (PLoS ONE, 2025)
Background Avascular necrosis (AVN) of the hip is a disease characterized by vascular disruptions, where 67% of untreated cases may lead to the collapse of the femoral head. None of the current approaches, such as core decompression (CD), vascularized bone grafting, osteotomy, tissue implantation, and other methods, have been proven fully effective in delaying the progression of osteonecrosis. Recent findings indicate that bone marrow stem cells (BMSCs) have significant potential to regenerate necrotic tissue and prevent the progression of AVN in the hip. This study aims to evaluate the efficacy, side effects, treatment failure rate, most effective treatment stage of AVN hip, and application technique to treat AVN hip. Method We performed this systematic review and meta-analysis from randomized controlled trials (RCTs) and sources published between 2013 and 2023 from six databases. The literature searching method was based on predetermined PICOS, study eligibility criteria, and PRISMA guidelines. The extracted data were then assessed quantitatively using R Studio with Harris hip score (HHS), Visual analog scale (VAS), the collapse of the femoral head, and conversion of total hip arthroplasty (THA) as the outcomes of interest, then qualitatively using RoB Tool, the extracted data were analyzed using R Studio. Result A total of 12,939 records were identified through database searching. After the removal of duplicates and non-randomized studies using automation tools, 4,846 articles were screened. Following title and abstract review, 10 studies met the eligibility criteria and were included in the systematic review and meta-analysis, comprising 593 patients and 779 hips. The included studies originated from China (n = 4), France (n = 1), South Korea (n = 1), Australia (n = 1), Iran (n = 1), India (n = 1), and Spain (n = 1). Risk of bias assessment using RoB 2.0 tool revealed 70% of the RCTs were rated as having a low risk of bias, while 30% were judged to have some concerns. Meta-analysis demonstrated that BMSC therapy significantly reduced the risk of femoral head collapse (OR = 0.15; 95% CI: 0.09–0.25; P < 0.00001; I² = 0%) and conversion to THA (OR = 0.20; 95% CI: 0.13–0.31; P < 0.00001; I² = 83%). Functional outcomes, as measured by the HHS, were significantly improved in the BMSC group (MD = 10.70; 95% CI: 9.70–11.69; P < 0.00001; I² = 51%). Pain reduction, assessed using the VAS, also favored BMSC therapy (MD = −8.04; 95% CI: −8.66 to −7.42; P < 0.00001; I² = 99%). Meta-regression analyses explored the influence of study-level covariates on outcomes. No predictor reached statistical significance for HHS or THA conversion. However, mean age showed a borderline significant association with VAS (coefficient = −0.8029; P = 0.065), suggesting a possible trend of more significant pain reduction in older patients. Conclusion Currently established AVN hip treatments are proven to be less effective. The findings strongly support that giving a BMSC at the early-stage AVN hip could improve the patient’s clinical outcome and have fewer side effects and treatment failure compared to conventional treatment.